Oral Mucosal Ulcer Associated with Improper Usage of Bisphosphonate: A Case Report - Şeyma Nur Bayındır; Bilinç Doğruöz Karatekin; Afitap İçağasıoğlu (Galenos Yayinevi, 2023)
Bisphosphonates are widely used agents for osteoporosis. Although bisphosphonates are generally well-tolerated drugs, especially oral forms may have gastrointestinal system side effects. Oral bisphosphonate-induced oral mucosal injury, oral ulcers, vesicles, and gingivitis are rarely reported in the literature. Lesions related to improper usage of bisphosphonates are atypical and need to be differentiated from other mucosal erosions. In this report, a case of painful, hemorragic oral ulcer in the soft palate in a patient with osteoporosis is discussed in light of the relevant literature.